Pemberdayaan Masyarakat dalam Pemanfaatan Buah Pepaya Muda dan Wortel untuk Peningkatan Produksi ASI pada Ibu Menyusui di Desa Kademangan, Jambi - Nurmisih Nurmisih; Titik Hindriati; Nuraidah Nuraidah; Ry Eny Mian Marisi. S (Jurnal Abdimas Kesehatan (JAK), 2022)
Infants aged 0-6 months need adequate nutritional intake to support growth and development. These nutritional needs are highly dependent on breast milk (ASI). In breastfeeding mothers, problems often occur such as insufficient milk production and mothers do not understand the correct lactation management. Lactagogum and vitamin A play a role to help increase milk production. One of the fruits that contain laktagogum is young papaya, and carrots are foodstuffs that contain vitamin A. Young papaya and carrots are easily available foodstuffs. When the initial survey was conducted, most of the posyandu cadres and breastfeeding mothers in Kademangan village did not know the benefits of young papaya and carrots to help increase breast milk production for children. Community empowerment activities through posyandu are one solution to increase community knowledge in the use of young papaya and carrots to help increase production. This service activity was carried out in Kademangan Village, Jambi District outside the City, aiming to increase public knowledge in the use of young papaya and carrots to help increase breast milk production for breastfeeding mothers. The target of service is posyandu cadres (how many prang) and 30 nursing mothers. The flow of service before the activity was carried out by a pretest, then counseling and pocket books were given, followed by the practice of processing food made from young papaya and carrots, then a post test was carried out. The results of the activity showed an increase in the average score of knowledge in general before and after providing counseling to posyandu cadres and breastfeeding mothers. The average score of prior knowledge of posyandu cadres before the intervention was 7.60 increased to 9.80 and the average score of early knowledge of breastfeeding mothers was 7.60 increased to 9.86.